International Cooperative Development of Techniques for Sustainability when Managing and Restoring Degraded Rangelands - Yespolov, Tlektes; Beksultanov, Marat; Strohmeier, Stefan; Haddad, Mira; Weltz, Mark; Nouwakpo, Sayjro; Spaeth, Kenneth; Burns, Ian; Arslan, Awadis; Toledo, David; Nesbit, Jason (2018)
In the United States 20% of privately owned rangelands are vulnerable to accelerated soil loss. Estimated annual costs of direct and indirect damage caused by soil erosion in the United States is $27 billion dollars. More than 50% of Asia and 70% of Middle Eastern rangelands are degraded. Exact estimates of economic costs and total area degraded is unknown; however, costs may be significantly higher than in the United States due to the extent of degradation/desertification in these regions. United States Department of Agriculture (USDA) scientists and its partners are working with Kazakh National Agrarian University in Kazakhstan and the International Center for Agricultural Research in Dry Areas (ICARDA), Jordan to develop a multiphase approach to validate and deploy various rangeland assessment technologies to address rangeland degradation/desertification by soil erosion and enhance food and water security.